Impact of Covid on the Global Economy in Tourism Perspective (Journal of Informatics Education and Research, 2024)
Corona virus has become the most dangerous disaster of the twenty-first century. All the sectors in t whole world ha dot stopped functioning, which leads the global GDP and many more factors to have anise dive. The majority of the developed countries had faced huge loose, and their economies had to face a downfall in trade, FDI, import-Export ratio and many more vital aspects of the economy. The study is going to find out exciting data related to the financial aspect of the countries. The data will be collected by the secondary data collection method due to the high quantity of data and then the data is going to be sorted out by the exclusion and inclusion method. Then the data are going to be analyzed to find out t exact stage of the country or global economy at that time especially in the tourism sector all over the world. The research article is going to be very helpful for the researchers and the statistical data is going to be very helpful for further research.